Combined MitraClip implantation and left atrial appendage occlusion using the Watchman device : a case series from a referral center - Francisco, Ana Rita G. (2018)
© 2017 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. All rights reserved.